Narrative coping with radical experiences of a returner in the German and Turkish environments [Narrative Bewältigung von einschneidenden Erlebnissen eines Rückkehrers in der deutschen und tüirkischen Lebenswelt] - (:unkn) unknown (Erich Schmidt Verlag GmbH and Co Berlin, 2019)
This article is based on data from my biographically and interactionally oriented pilot study on the socio-linguistic experiences of "returners", i. e. young men and women of Turkish origin who grew up in Germany or Austria and who migrated to Turkey as young adults. Furkan, the informant who figures here, describes experiences of exclusion in Germany because of his ethnic background, and problems in adjusting to life in Turkey because of his social and linguistic conspicuousness. The aim of my analysis is to describe the different phases of his biography in the two different environments, to reconstruct the relationship between experiences of exclusion in both environments, the ways they are interpreted and presented in his narrative, and finally to analyse the differences of the narratives referring to one or the other environment. On the basis of all of this, Furkan's narratives about his experiences as a child in Germany may be related to narrative forms characteristic of coping with traumatic experiences. © 2019 Erich Schmidt Verlag GmbH and Co Berlin. All rights reserved.